PERANCANGAN APLIKASI REKAM MEDIS PADA PUSKESMAS TALANG TINGGI - Niska Ramadani; Fadlul Amdhi Yul (LPPM Politeknik Jambi, 2019)
Information technology is currently growing fast, which allows users to receive information quickly. Users needs is different,, such as communication, education, business, entertainment, economy, health and others. One example of its users in the health sector is the medical records information system. Medical record is a collection of facts or evidence of a patient's condition, past and present medical history and treatment written by the health professionals that provides patient care. The objective to be achieved in this research is to make a medical record application of patients at Puskesmas Talang Tinggi using programming language Visual Basic 6.0 The research method used in this research is from conventional system to computerized system with the stages is old system analysis, new system analysis, system design, system implementation and system test. The software used in making this application is visual basic and using microsoft access database. The results of the report in the show using crystal report.